Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jid.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

IL-17E (IL-25) Enhances Innate Immune Responses during Skin Inflammation

Abstract: IL-17E (IL-25) is a member of the IL-17 cytokine family involved in the promotion of type 2 immune responses. Recently, IL-17E has been reported to be up-regulated in distinct skin inflammatory diseases such as psoriasis and atopic and contact dermatitis. We assessed the role played by IL-17E in skin inflammation. Here, we show that IL-17E induces skin inflammation in vivo, characterized by the expression of innate immune response genes and the recruitment of innate immune cells, particularly neutrophils. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 50 publications
3
41
0
3
Order By: Relevance
“…In atopic dermatitis, IL-17E was shown to impair the proper epidermal barrier formation (Deleuran et al, 2012;Hvid et al, 2011). In psoriasis, we identified that keratinocytes overproduce IL-17E, leading to inflammatory events favoring the recruitment of neutrophils (Senra et al, 2019(Senra et al, , 2016. Later studies confirmed our observations and reported an autocrine function for IL-17E in mouse keratinocytes (Xu et al, 2018).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In atopic dermatitis, IL-17E was shown to impair the proper epidermal barrier formation (Deleuran et al, 2012;Hvid et al, 2011). In psoriasis, we identified that keratinocytes overproduce IL-17E, leading to inflammatory events favoring the recruitment of neutrophils (Senra et al, 2019(Senra et al, , 2016. Later studies confirmed our observations and reported an autocrine function for IL-17E in mouse keratinocytes (Xu et al, 2018).…”
Section: Introductionsupporting
confidence: 75%
“…IL-17A is likely the most important factor driving psoriasis, as demonstrated by the high efficacy of antieIL-17A targeted therapies (Yiu and Griffiths, 2016). Previously, we demonstrated that IL-17E amplifies the inflammatory loop in psoriasis by acting on immune cells (Senra et al, 2019(Senra et al, , 2016. Here we document the capacity of IL-17E to target keratinocytes in an autocrine manner.…”
Section: Discussionsupporting
confidence: 54%
“…IL-17A and IL-17F are significantly implicated in immune responses to infectious pathogens and in the pathogenesis of inflammatory autoimmune diseases like psoriasis. Furthermore, evidence indicates an additional proinflammatory activity of IL-17C and IL-17E within the pathogenesis of psoriasis (18)(19)(20)(21).…”
Section: Biology Of Il-17a and Il-17fmentioning
confidence: 99%
“…The T helper 17 (Th17) cells constitute a unique subset of CD4 + T cells and are the major source of IL-17 (5). IL-17A triggers cellular reactions not only in the keratinocytes, but also in some other cells, including neutrophils, endothelial cells, fibroblasts, and osteoclasts (6)(7)(8)(9)(10). In keratinocytes, the binding of IL-17A to IL-17 receptor (IL-17R) A, IL-17C, or IL-17RD stimulates keratinocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%